Bioactive metabolites of Blumea lacera attenuate anxiety and depression in rodents and computer‐aided model. Issue 7 (31st May 2021) - Hossen, Md. Amjad; Ali Reza, A.S.M.; Amin, Md. Badrul; Nasrin, Mst. Samima; Khan, Tawhidul Amin; Rajib, Md. Habibur Rahman; Tareq, Abu Montakim; Haque, Md. Anwarul; Rahman, Md. Atiar; Haque, Md. Areeful
Abstract: Blumea lacera is an edible plant with imperative medicinal values. However, the anxiolytic and antidepressant roles of B. lacera have not been well‐explained. Therefore, the current study aims to explore the impending bioactive metabolites and roles of B. lacera methanol leaf extract (Me‐BLL) in attenuating anxiety and depression through several experimental and computer‐aided approaches. The chemical characterization of Me‐BLL was performed through standard phytochemical and GC‐MS analyses. To explore the neuropharmacological insights, Swiss albino mice were treated with Me‐BLL at doses of 200–400 mg/kg, p.o. The anxiolytic effects were observed employing elevated plus maze (EPM), light–dark box (LDB), and hole‐board (HBT) tests, while antidepressant effects were evaluated using forced swimming (FST) and tail suspension tests (TST). Diazepam (1 mg/kg, i.p.) and fluoxetine HCl (20 mg/kg, p.o.) were used as the reference standard. The phytochemical analyses revealed several bioactive metabolites, including higher contents of total phenolics and flavonoids. The EPM and LDB tests demonstrated an increased time spent in open arms and light box, and the HBT showed an increased number of head dipping, indicating the anxiolytic effects of Me‐BLL. The TST and FST revealed a decrease in immobility time, meaning the persuasive antidepressant effects. The antioxidative effects of Me‐BLL have also been observed prominently. Correspondingly, the computer‐aided investigation confirmed several bioactive lead molecules. Specifically, thymol and cuminol revealed potential anxiolytic and antioxidant effects, while stigmast‐5‐en‐3.beta.‐ol and gamma‐sitosterol possessed promising antidepressant effects. Taken these results as a base, the plant has imperative potentials in managing anxiety and depression‐like disorders. Abstract : Chemical analysis revealed wide range of bioactive metabolites including phenolics and flavonoids in Me‐BLL. Me‐BLL produced promising anxiolytic effects in EPM, LDB, and HBT in experimental rodents. Me‐BLL revealed significant reduction of immobility time in FST and TST. Lead molecules like cuminol, thymol, and γ‐sitosterol revealed potentials in computer‐aided model.